The Future of .NET Core, Machine Learning, and AI - Jagdip Keshavlal Jadav, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The integration of Machine Learning and Artificial Intelligence into the .NET Core ecosystem represents a significant advancement in software development capabilities. This comprehensive article examines the evolution of AI integration within .NET, highlighting key developments across multiple domains including ML.NET enhancements, generative AI capabilities, and the introduction of Microsoft.Extensions.AI. The article explores how these advancements have transformed developer workflows, improved performance metrics, and expanded the possibilities for AI-driven applications. Through a detailed examination of implementation patterns, performance improvements, and community engagement, this article demonstrates how the .NET ecosystem has emerged as a robust platform for AI development, supported by Microsoft's comprehensive educational resources and strong community infrastructure.
Keywords: ML.NET; Generative AI Integration; Microsoft.Extensions.AI; .NET Core Development; Azure Cognitive Services